Is Physical Abuse or Blue Sclera? A Case Report - Korkmaz, Bedir; Özkök, Mustafa Selim; Kallem, Füsun Çallak; Dirlik, Musa; Katkıcı, Ufuk (The Bulletin of Legal Medicine, 2017)
Abuse of the children continues to be an important problem of public health and social welfare. Approximately 4-16% of all children are exposed physical abused and 155.000 children worldwide lost their life cause of the abuse and neglect in each year. It is usually difficult to distinguish the skin diseases that mimics maltreatment and child abuse for clinicians. To distinguish between these two conditions a dermatologist may be consulted. Because skin damage is the most recognizable and common form of the abuse. A seven years old girl who have been subjected to physical abuse by her father according to the hospital records and sent to our clinic for the evaluation of lesions on the face and body in terms of congenital or a sign of physical abuse has investigated in this study. Patient was consulted to pediatrics, dermatology and ophthalmology. It was found that the vision is normal, no retinal damage and blue sclera (thinning of the retina) was detected. The lesions on face and body were consistent with the port-wine stains. These findings on face and body were not associated with physical abuse. It is highlighted in this study that the lesions of skin disease and some metabolic diseases should be considered in the differential diagnosis of physical abuse.